Convergence of Row Sequences of Simultaneous Padé–Faber Approximants - N. Bosuwan (2019)
© 2018, Pleiades Publishing, Ltd. We consider row sequences of vector valued Padé-Faber approximants (simultaneous Padé–Faber approximants) and prove a Montessus de Ballore-type theorem.